2009
DOI: 10.1504/ijfipm.2009.027591
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic simulation on personalised heart-torso structures using coupled meshfree-BEM platform

Abstract: The foremost premise for the success of noninvasive volumetric myocardial Transmembrane (TMP) imaging from Body Surface Potential (BSP) recordings is a realistic yet efficient TMP-to-BSP mapping model that balances model accuracy with reconstruction feasibility. This papers presents a novel coupled meshfree-BEM platform to this forward electrocardiographic modelling. Its numerical accuracy and convergence is quantitatively assessed against analytical solutions on a synthetic geometry. Electrocardiographic simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…In this study, (3) and (4) are solved with the coupled meshfree and boundary element methods [29], [30]. The value of anisotropic intracellular conductivity tensor , bulk conductivity , and torso conductivity are adopted from [31].…”
Section: Forward Problem Of Electrocardiographymentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, (3) and (4) are solved with the coupled meshfree and boundary element methods [29], [30]. The value of anisotropic intracellular conductivity tensor , bulk conductivity , and torso conductivity are adopted from [31].…”
Section: Forward Problem Of Electrocardiographymentioning
confidence: 99%
“…Therefore, we define an alternative approximation of the continuous form of TV as (10) where a numerical integration is performed over the 3-D myocardial field by (at the order of ) Gaussian quadrature points. Depending on the discretization method used (such as the finite element method or meshfree method [33] used in our study [29], [30]), on each Gauss point is approximated by a linear combination of its neighboring nodal points in the discrete field based on the spatial gradient of the shape function . Because each Gauss point has only a small set of support nodal points, and are sparse with a small number of nonzero values.…”
Section: A Variational Tv-priormentioning
confidence: 99%
See 2 more Smart Citations
“…The Laplace equation (2) describes, on the monodomain torso model, how the potential φ distributes within the torso volume Ω t/h external to the heart with conductivity σ. It has been previously shown that, using proper numerical methods such as mesh free and boundary element methods, one can numerically solve equation (1,2) on a subject heart-torso model, and obtain linear relationship: b = Hv [11].…”
Section: Methodsmentioning
confidence: 99%